2021
DOI: 10.1021/acsami.0c19435
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly AgBiS2 Nanocrystal/ZnO Nanowire Heterojunction Solar Cells with Enhanced Carrier Collection Efficiency

Abstract: AgBiS 2 nanocrystals (NCs) are nontoxic, lead-free, and near-infrared absorbing materials. Eco-friendly solar cells were constructed using interdigitated layers of ZnO nanowires (NWs) and AgBiS 2 NCs, with the aim of elongating the otherwise short carrier diffusion length of the AgBiS 2 NC assembly. AgBiS 2 NCs were uniformly infiltrated into the ZnO NW layers using a low-cost and easily scalable dip coating method. The resulting ZnO NW/AgBiS 2 NC interdigitated structures provided efficient carrier pathways i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…46 Tetrabutylammonium iodide (TBAI) ligand-exchanged PbS CQDs (referred to as I-ligand PbS QD)/ZnO NW interdigitated structures were formed on F-doped SnO 2 (FTO) substrates (Figure 1b) using a layer-by-layer dip-coating deposition method. 47 An Iligand PbS QD thin capping layer was also dip-coated to ensure a complete infiltration into the ZnO NWs. Besides facilitating the infiltration of QDs, dip-coating deposition precisely controls the layer thickness control, which is essential for fabricating the interdigitated structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Tetrabutylammonium iodide (TBAI) ligand-exchanged PbS CQDs (referred to as I-ligand PbS QD)/ZnO NW interdigitated structures were formed on F-doped SnO 2 (FTO) substrates (Figure 1b) using a layer-by-layer dip-coating deposition method. 47 An Iligand PbS QD thin capping layer was also dip-coated to ensure a complete infiltration into the ZnO NWs. Besides facilitating the infiltration of QDs, dip-coating deposition precisely controls the layer thickness control, which is essential for fabricating the interdigitated structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…PbS CQDs with a first exciton absorption peak at 950 nm were synthesized by a previously reported method . Tetrabutylammonium iodide (TBAI) ligand-exchanged PbS CQDs (referred to as I-ligand PbS QD)/ZnO NW interdigitated structures were formed on F-doped SnO 2 (FTO) substrates (Figure b) using a layer-by-layer dip-coating deposition method . An I-ligand PbS QD thin capping layer was also dip-coated to ensure a complete infiltration into the ZnO NWs.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years there has been a remarkable progress in the synthesis and application of colloidal AgBiS 2 nanocrystals as the photoactive material in solar cell devices. 7,11,12,[17][18][19][20][21][22][23]24 The low carrier diffusion length and the non-negligible recombination pathways have been identified as the main limiting factors for photocurrent generation, especially when using thick active layers. 7,12 Therefore, the record solar cell efficiencies reported so far typically limit the optimal AgBiS 2 layer thickness at around 35 nm.…”
Section: Enhanced Solar Cell Performancementioning
confidence: 99%
“…Nanowires of ZnO have also been incorporated into AgBiS 2 devices for enhanced carrier collection and diffusion lengths, providing higher EQE (82%) values over the EQE (41%) observed for control ZnO/AgBiS 2 NCs. 62 Oxygen vacancies in ZnO nanowires play an important role in determining the structural order of these materials and it has been found that a lower concentration of vacancies enables weaker electron–phonon interaction and can enhance the carrier collection from AgBiS 2 SCs. 65 Even though ZnO is a stable material, the spin coating method of ZnO deposition, if carried out in open air, allows accumulation of physiosorbed water, thus instigating AgBiS 2 NCs to decompose into silver sulfide and bismuth oxide.…”
Section: Influence Of Adjacent Charge Transport Layersmentioning
confidence: 99%